PROFILE OF FATAL POISONING IN AUTOPSY CASES AT A TERTIARY CARE HOSPITAL IN PORT BLAIR (ANDAMAN AND NICOBAR ISLANDS): A SEVEN-YEAR RETROSPECTIVE STUDY (Journal of Forensic Medicine & Toxicology, 2025)
Poisoning is a significant worldwide public health concern. According to the National Crime Records Bureau (NCRB) 2022 report, there is an increase in the number of suicides and suicide rate in India, in 2022 from 2021. The present study was a retrospective study conducted to determine the profile of fatal poisoning. A total of 65 fatal poisoning cases brought for autopsy at the Mortuary of the Department of Forensic Medicine & Toxicology, ANIIMS & G.B. Pant Hospital, Port Blair, Andaman & Nicobar Islands from January 2016 to December 2022 were analyzed. Gender-wise, the victims included 49 (75.4%) males and 16 (24.6%) females, the majority of whom were married. The maximum poisoning
Keywords: Poisoning; Andaman & Nicobar Islands